Pazopanib in Patients with Osteosarcoma Metastatic to the Lung: Phase 2 Study Results and the Lessons for Tumor Measurement. (15th January 2022) - Frankel, Paul; Ruel, Chris; Uche, An; Choy, Edwin; Okuno, Scott; Somiah, Neeta; Chow, Warren A.
Abstract : Background . This single-arm, multicenter, phase 2 study evaluated the safety and antitumor activity of pazopanib in patients with unresectable, pulmonary metastatic osteosarcoma. Patients and Methods . Patients with pulmonary metastatic osteosarcoma unresponsive to chemotherapy were eligible. Patients who received prior tyrosine kinase inhibitor therapy were excluded. Pazopanib at 800 mg once daily was administered for 28-day cycles. Tumor responses were evaluated by local radiology assessment 1 month prior to and after initiation of treatment to calculate tumor doubling time and after every even numbered cycle. The primary endpoints were progression-free survival at 4 months, concomitant with a demonstrated 30% increase in tumor doubling time relative to the pretreatment growth rate. Results . 12 patients (7 female) were enrolled. The study was terminated prematurely due to withdrawal of financial support by the sponsor. 8 subjects were eligible for the primary analysis, whereas 4 patients were in a predefined exploratory "slow-growing" cohort. In the "fast-growing" cohort, 3 of the 8 patients (37.5%) eligible for first-stage analysis were deemed "success" by the preplanned criteria, adequate to proceed to second-stage accrual. In addition, 1 of the 4 patients in the "slow-growing" cohort experienced a partial remission. Grade 1-2 diarrhea was the most common adverse event, and grade 3 events were infrequent. Conclusion . This study illustrates a novel method of demonstrating positive drug activity in osteosarcoma by increasing tumor doubling time, and this is further supported by a partial response in a patient with "slow-growing" disease. This trial is registered with NCT01759303 .